Defective ciliogenesis in INPP5E‐related Joubert syndrome. Issue 12 (20th October 2017) - Hardee, Isabel; Soldatos, Ariane; Davids, Mariska; Vilboux, Thierry; Toro, Camilo; David, Karen L.; Ferreira, Carlos R.; Nehrebecky, Michele; Snow, Joseph; Thurm, Audrey; Heller, Theo; Macnamara, Ellen F.; et al.
Abstract : Joubert syndrome is a neurodevelopmental disorder, characterized by malformation of the mid and hindbrain leading to the pathognomonic molar tooth appearance of the brainstem and cerebellum on axial MRI. Core clinical manifestations include hypotonia, tachypnea/apnea, ataxia, ocular motor apraxia, and developmental delay of varying degrees. In addition, a subset of patients has retinal dystrophy, chorioretinal colobomas, hepatorenal fibrocystic disease, and polydactyly. Joubert syndrome exhibits genetic heterogeneity, with mutations identified in more than 30 genes, including INPP5E, a gene encoding inositol polyphosphate 5‐phosphatase E, which is important in the development and stability of the primary cilium. Here, we report the detailed clinical phenotypes of two sisters with a novel homozygous variant in INPP5E (NM_019892.4: c.1565G>C, NP_063945.2: p.Gly552Ala), expanding the phenotype associated with Joubert syndrome type 1. Expression studies using patient‐derived fibroblasts showed changes in mRNA and protein levels. Analysis of fibroblasts from patients revealed that a significant number of cells had shorter or no cilia, indicating defects in ciliogenesis, and cilia maintenance.